Análise do trabalho em uma unidade de alimentação e nutrição do tipo autogestão: um estudo de caso - Jardim, Maria de Fatima de Barros (2005)
The work, mainly a case study, presents a study concerning safety and health 's conditions of workers at a Feeding and Nutrition Unit (UAN), which produces daily, on average, three thousand meals. The main objective of the research was to verity the influence of working conditions on the safety and health of UAN's workers. The methodology employed included: i. The observation of attendance's activities; ii. Informal interviews with the nutritionist's manager and planning and production nutritionists; iii. The application of questionnaires to other workers and productive process' operators which included questions about personal qualifications, employment's contract, health's conditions, qualitative environmental conditions and evaluation of work organizing situations. Morcover, an observation of working norms and regulations made possible to identify risk's factors, such as physical occupational ones, organizational and ergonomically ones, and accidents that interfere in the health and safety of these workers. The work also presents considerations and recommendations that seek to contribute to improving life quality of the UAN's workers investigated, it also presents suggestions for future works